Effectiveness of Village Fund Policy in Economic and Infrastructure Development in Pringgajurang Village, Montong Gading District - Siti Nurhidayati; Muaidy Yasin; Iwan Harsono (Future Tecno-Science Publisher, 2025)
This study aims to determine the effectiveness of village fund policies in economic and infrastructure development in Pringga Jurang Village, Montong Gading District. This study aims to determine and analyze the extent to which the effectiveness of the Village Fund policy in economic and infrastructure development in Peringge Jurang Village. This study uses a combination method approach (Mixed Methods), namely by combining qualitative and quantitative methods in order to analyze facts and events with the use of Village Fund Effectiveness. The population and sample in this study were the Peringge Jurang community with 95 samples. The results of this study indicate that the Effectiveness of the Village Fund Policy in Economic and Infrastructure Development in Pringga Jurang Village has been effective. This can be seen from the first planning indicator with a score of 80.78% which indicates that the village government in planning economic and infrastructure development has been effective. The second implementation indicator with a score of 79.78º which indicates that the process of implementing economic and infrastructure development has been effective. The third indicator of supervision and transparency with a score of 80.86% which indicates that the transparency reporting process has been effective.